Tretatment approach of nontransplant patients with multiple myeloma - Krstevska Balkanov, Svetlana; Sotirova, Tatjana; Balkanov, Trajan; Genadieva Stavrikj, Sonja (ScopeMed, 2014)
Multiple myeloma is still an incurable disease with pattern of regression and remission followed by multiple relapses raising from the residual myeloma cells surviving even in the patients who achieve complete clinical response to treatment. In recent years there is a huge improvement in treatment of patients with multiple myeloma. The milestones of these improvement are: autologous transplantation and high-dose melphalan, imunomodulating drugs (thalidomide, lenalidomide), proteosom inhibitors (bortesomib, carfilzomib). The most significant improvement in overall survival has been achieved in the patients younger than 65 years. So, the major challenge for hematologist is to translate this improvement in the elderly patients with multiple myeloma. Today, physicians are able to offer wider variety of treatment options for elderly patients with multiple myeloma. Therapeutic options should be tailored and personalized according to patient's characteristics by balancing efficacy and toxicity of each drug which is especially important for elderly patients. In the mode of sequencing treatment for elderly patients with multiple myeloma, our goal is to achieve and maintain maximal response while limiting treatment -related toxicities as much as possible. Second-generation novel agent, such as carfilzomib, pomalidomide, elotuzumab, bendamustine are currently being evaluated as an option to improve treatment outcome in elderly patients.